(untitled) (REMUNOM, 2026)
This article investigates how Afro-Brazilian children’s and young adult literature can contribute to the implementation of anti-racist education in early childhood education and the initial years of elementary school, taking as its central question how the systematic inclusion of these works impacts the construction of identities, the development of Afro-literacy, and the approach to ethnic-racial relations in the school context. A qualitative approach is adopted, structured from a bibliographic review, an analysis of the work Julia no Jardim dos Orixás (2019), by Thiago Pugliesi Carvalho, and an exploratory study with teachers from the public school system of Linhares (ES). The results indicate that, although there is recognition of the importance of Laws No. 10.639/2003 and No. 11.645/2008, their implementation remains fragmented. The analysis of the work highlights its pedagogical potential in valuing Afro-Brazilian culture and confronting religious racism. It is concluded that Afro-Brazilian literature, when integrated in a continuous and critical way, constitutes a central tool for the consolidation of anti-racist pedagogical practices.